Neuroinflammation of traumatic brain injury: Roles of extracellular vesicles - Liu, Xilei; Zhang, Lan; Cao, Yiyao; Jia, Haoran; Li, Xiaotian; Li, Fanjian; Zhang, Shu; Zhang, Jianning (Frontiers in Immunology, 2023)
Traumatic brain injury (TBI) is a major cause of neurological disorder or death, with a heavy burden on individuals and families. While sustained primary insult leads to damage, subsequent secondary events are considered key pathophysiological characteristics post-TBI, and the inflammatory response is a prominent contributor to the secondary cascade. Neuroinflammation is a multifaceted physiological response and exerts both positive and negative effects on TBI. Extracellular vesicles (EVs), as messengers for intercellular communication, are involved in biological and pathological processes in central nervous system (CNS) diseases and injuries. The number and characteristics of EVs and their cargo in the CNS and peripheral circulation undergo tremendous changes in response to TBI, and these EVs regulate neuroinflammatory reactions by activating prominent receptors on receptor cells or delivering pro- or anti-inflammatory cargo to receptor cells. The purpose of this review is to discuss the possible neuroinflammatory mechanisms of EVs and loading in the context of TBI. Furthermore, we summarize the potential role of diverse types of cell-derived EVs in inflammation following TBI.